ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN PEMBELIAN KENTANG DI PASAR TRADISIONAL KOTA BOGOR - Veralianta Br Sebayang; Nabila Rahmania Az Zahra; Diyah Puspa Asih Atsilanti; Devi Pradipta Kartika Buana; Muhammad Faishol Jahiddudin; Abib Riyadi; Tasya Angelita (Politeknik Bisnis Indonesia, 2024)
Potatoes are an important food source, and understanding the factors that influence purchasing decisions in both traditional and modern markets is crucial for business owners to boost sales. This study aims to analyze the influence of price, distance, income, education, and occupation on consumer behavior in purchasing potatoes at Traditional Market, Bogor City. The research employs a quantitative approach using multiple linear regression analysis. The study was conducted from March to April 2024, with a sample of 86 respondents selected using the Slovin formula. The results indicate that price, distance, income, and occupation significantly influence consumer purchasing behavior, while education does not show a significant effect. The coefficient of determination (R square) obtained is 0.91512, indicating that approximately 91% of consumer purchasing behavior for potatoes can be explained by the variables studied. This research provides insights for market vendors in devising effective sales strategies based on the factors influencing consumer behavior.